Turmeric (Curcuma longa) Decoctum Had no Effect on Vascular Endothelial Growth Factor (VEGF) and Vascular Endothelial Cadherin (VE-cadherin) Expression in the Chick Embryo - Sri Winarsih; I Wayan Arsana Wiyasa; Sri Andarini; Sumarno Reto Prawiro (Research Journal of Life Science, 2018)
Turmeric (Curcuma longa) as a medicinal plant has widely consumed by pregnant women. The absence of dose standardization and the regulation of turmeric consumption in pregnancy raise concerns, especially if taken in early pregnancy. Angiogenesis is the process of new blood vessel formation from previously existing blood vessels, and plays an important role in embryogenesis and placentation during pregnancy. Angiogenesis is regulated by angiogenic molecules, such as VEGF and VE-cadherin. Turmeric has antiangiogenic effects in which the crude extract is pharmacologically more potent compared to the pure curcumin form. This study aimed to determine whether a turmeric decoctum affects the expression of VEGF and VE-cadherin in chick embryos. Turmeric was extracted by the decoction and freeze dried methods to obtain turmeric decoctum powder. This was tested on embryonated chicken eggs, which were divided into four groups; control group (2% DMSO) and treatment groups receiving various doses of the turmeric decoctum (200 ppm, 300 ppm and 400 ppm). The eggs used were less than 7 days after oviposition and incubated for 16 hours prior to injection of the treatment solution in ovo to the center of the yolk, followed by reincubation for up to 48 hours. Intraembryonic VEGF and VE-cadherin expression were assessed by whole-mount immunohistochemistry and quantified using image analysis techniques. This study showed administration of turmeric decoctum up to 400 ppm had no effect on the expression of VEGF and VE-cadherin in chick embryos.